Depositional Environment and Microfacies Analysis of Yamama Formation in North Rumaila Oil Field, South Iraq - Mohammed, Noor Alhuda; Nasser, Medhat E. (Iraqi Journal of Science, 2022)
Yamama Formation is an important sequence in southern Iraq. Petrographic analysis was used to determine and analyze the microfacies and pore types. The diagenetic processes and the impacts on the petrophysical properties of the rocks were also identified. The petrographic identification was based on data of 250 thin sections of cutting and core samples from four wells that were supplied by the Iraqi Oil Exploration Company (O.E.C). The present study focuses on the depositional environment and the microfacies analysis of Yamama Formation. The results revealed several types of microfacies, including peloidal wackestone-packstone, algal wackestone-packstone, bioclastic wackestone-packstone, foraminiferal wackestone, bioclastic wackestone, and mudstone. The latter was divided into two submicrofacies, namely argillaceous lime mudstone and sparse fossiliferous lime mudstone. The study showed that Yamama Formation was deposited through various settings within the carbonate platform; these comprise inner ramp, middle ramp, and outer ramp settings. The inner and middle ramp settings, characterized at the top and middle Formation, have high effective porosity and low clay volume, due to dominant packstone.